Determination of thermodynamic properties of poly [(2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate] by inverse gas chromatography - Ilter, Z; Kaya, I; Açikses, A (Freund Publishing House Ltd, 2002)
Some thermodynamic quantities such as the sorption enthalpy, DeltaH(1)(s), sorption free energy, DeltaG(1)(s), sorption entropy, DeltaS(1)(s), the partial molar free energy, DeltaG(1)(infinity), the partial molar heat of mixing, DeltaH(1)(infinity), at infinite dilution were obtained for the interactions of poly [(2-phenyl-1, 3-dioxolane-4-yl)methyl methacrylate] with alcohols, amines, benzene and n-alkanes by inverse gas chromatography method in the temperature range of 363-453 K. The specific retention volumes, Vgdegrees, the weight fraction activity coefficients of solute probes at infinite dilution, Omega(1)(infinity), Flory-Huggins interaction parameters, chi(12)(infinity) between polymers and solvents were determined. Also, The solubility parameters, delta(2), of the polymer found to be 6.21 (cal cm(-3))(0.5) and 6.23 (cal cm(-3))(0.5) from slope and intercept of [(delta(1)(2)/RT) - chi(infinity) (12)/V-t] (2delta(2)/RT) delta(1)-delta(2)(2)/RT equation, at 443 K, respectively. The glass transition temperature, Tg, of the polymer found to be 403 K by inverse gas chromatography.
Keywords: poly [(2-phenyl-1,3-dioxolane-4-yl) methylmethacrylate]; inverse gas chromatography; polymer-solvent interactions